Resource-Abundance and Economic Growth in the U.S. - Elissaios Papyrakis; Reyer Gerlagh (Fondazione Eni Enrico Mattei (FEEM), 2004)
It is a common assumption that regions within the same country converge to approximately the same steady-state income levels. The so-called absolute convergence hypothesis focuses on initial income levels to account for the variability in income growth among regions. Empirical data seem to support the absolute convergence hypothesis for U.S. states, but the data also show that natural resource-abundance is a significant negative determinant of growth. We find that natural resource abundance decreases investment, schooling, openness, and R&D expenditure and increases corruption, and we show that these effects can fully explain the negative effect of natural resource abundance on growth.
Keywords: C21; O13; O51; Q33; 330; Natural resources; Growth; Transmission channels; Regionales Wachstum; Wirtschaftliche Konvergenz; Natürliche Ressourcen; USA